Five years of biochar amendment combined with reduced fertilization and irrigation improved the soil organic carbon composition and structure in a solonchak - Jin Pei; Yinku Liang; Lihua Xue; Kazem Zamanian; Shiren Sun; Wenwen Li; Sheng Zhang; Xiaoning Zhao (Scientific Reports)
Abstract Biochar application can increase cultivated soil organic carbon (SOC) and fertility, especially in saline‒alkali soils facing climate change and salinization. To evaluate the effects of biochar application on SOC composition and structure, a 5-year maize field trial (2019–2023) was conducted in the Tarim River Basin, involving seven treatments with the following respective mineral N inputs (kg N ha−1), irrigation levels (mm) and biochar amendments (t ha−1): CONTROL (untreated soil), LNLW (100, 140, and 0), LNLWB (100, 140, and 10), MNMW (200, 220, and 0), MNMWB (200, 220, and 10), HNHW (300, 320, and 0), and HNHWB (300, 320, and 10). The SOC characteristics were analyzed after harvest. The results revealed that LNLWB produced the greatest increases in SOC (+61%), mineral-associated organic carbon (+54%), light fraction organic carbon (LFOC) (+322%), heavy fraction organic carbon (+3.5%), alkyl carbon/alkoxyl carbon ratio (+40%) and maize yield (+16%) but resulted in the greatest reduction in dissolved organic carbon (-37%), pore probability entropy (-0.8%) and fractal dimension (-6%). Biochar application increased SOC through increased LFOC and soil porosity and increased SOC stability through increased aromatic and humic properties, ultimately increasing yields. Biochar application resulted in significantly higher comprehensive scores (0.57~0.74) than treatments without biochar application (-0.56~-0.49) based on principal component analysis of the SOC content and structure, and LNLWB had the highest score. Under greater biochar contributions, even 2/3 reduced N input (LNLW) performed well and represented the best low-carbon strategy in saline‒alkali soils.